Group portrait of participants at the annual Bob Coyle Chevrolet Company picnic - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the 1952 annual picnic of the Bob Coyle Chevrolet Company, held at an unknown location.